A Note on Multi-Regional Marketing - Ingene, Charles A.; Parry, Mark E. (Management Science, 1995)
This paper examines the profit maximizing behavior of a vertically integrated firm that operates in “n” geographically distinct regions. A pair of alternative managerial decision scenarios are considered. In one scenario, all marketing mix variables are manipulated at the regional level, so that each region may choose different levels of each marketing variable. In the second scenario, one marketing variable is manipulated “globally,” so that its level is identical in all regions. The first scenario generates an n-region version of the “Dorfman-Steiner” first-order conditions for profit maximization. However, under some cost structures the profits associated with this Dorfman-Steiner scenario are dominated by those associated with the second, “Global-Regional” scenario. This second scenario yields an optimal solution in which the global marketing variable may have a negative marginal impact on sales in some regions. As a result, some managerial implications of the second scenario differ strikingly from those of the Dorfman-Steiner scenario.